A Critical Evaluation of UK Defined Benefit Pension Schemes Asset Allocation - Antha, Evelina (2010)
Following the economic crisis which resulted in uncertainty of trustees to meet pension obligations, institutional investors are becoming more conscious of investment risks. They risk getting less return than previously forecasted as a result of falling prices in the equity market. In turn to mitigate the risk, the investment strategy of the schemes has been greatly influenced. Pension schemes currently have a tendency to shift their investment strategy from return-seeking to a liability driven strategy. Moreover, researchers have reported that the UK ageing population will grow significantly within the next few years, thus there is an important recognition that pension schemes assets should also be increased considerably to provide sufficient income to meet pension obligations. The main issue for pension schemes investment managers is how to invest their assets to ensure that the funds will be available to pay pension obligations when due.